Occurrence and distribution of antibiotic resistance genes in the sediments of the East China Sea bays - Jiayu Chen; Su, Zhiguo; Dai, Tianjiao; Huang, Bei; Mu, Qinglin; Yongming Zhang; Wen, Donghui (Journal of Environmental Sciences, 2019)
The coastal area of the East China Sea has experienced rapid urbanization and industrialization in China since 1980s, resulting in severe pollution of its environments. Antibiotic resistance genes (ARGs) are regarded as a kind of emerging pollutant with potential high risk. The sediment samples were collected from Hangzhou Bay (HB), Xiangshan Bay (XB), and Taizhou Bay (TB) to investigate the spatial occurrence and distribution of 27 ARGs and class I integron–integrase gene (intI1) in the coastal area of the East China Sea. The PCR results showed the frequent presence of 11 ARGs and intI1 in the sediments of the three bays. The qPCR results further showed that sulfonamide resistance was the most prevalent ARG type and antibiotic target replacement and protection were the most important resistance mechanisms in the sediments. Regarding the subtype of ARGs, sulI, tetW, and dfrA13 were the most abundant ARGs, in which sulI was higher in TB (based on both the absolute and relative abundances) and dfrA13 was higher in HB (based on the relative abundances). The network analysis revealed that intI1 had significant correlations with tetC, sulI, sulII, and blaPSE-1. Oil was the key connected factor, which had positive connections with sulI, sulII, and blaPSE-1. In addition, the joint effect of heavy metals and nutrients & organic pollutants might be crucial for the fate of ARGs in the coastal sediments.